2023
DOI: 10.1002/jcp.31040
|View full text |Cite
|
Sign up to set email alerts
|

Y‐box binding protein 1 influences zygotic genome activation by regulating N6‐methyladenosine in porcine embryos

Abstract: Y-box binding protein 1 (YBX1) is a member of the family of DNA-and RNA-binding proteins that play crucial roles in multiple aspects, including RNA stabilization, translational repression, and transcriptional regulation; however, its roles in embryo development remain less known. In this study, to investigate the function of YBX1 and its mechanism of action in porcine embryo development, YBX1 was knocked down by microinjecting YBX1 siRNA at the one-cell stage. YBX1 is located in the cytoplasm during embryonic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 48 publications
0
1
0
Order By: Relevance
“…However, after YBX1 gene knockdown, it affects the stability of AS and RNA, thus leading to the development defects of pre-ZGA embryos. However, the difference is that studies on pigs, sheep, mice, zebrafish, and other species have shown that the development of embryos is affected by m6A modification, while the mechanism of the effect on cattle has not been reported [68][69][70][71]. CENPF, ZSCAN4, GLIS1, TEAD4, and CDX2 all inhibited the development of early ZGA to varying degrees.…”
Section: Discussionmentioning
confidence: 94%
“…However, after YBX1 gene knockdown, it affects the stability of AS and RNA, thus leading to the development defects of pre-ZGA embryos. However, the difference is that studies on pigs, sheep, mice, zebrafish, and other species have shown that the development of embryos is affected by m6A modification, while the mechanism of the effect on cattle has not been reported [68][69][70][71]. CENPF, ZSCAN4, GLIS1, TEAD4, and CDX2 all inhibited the development of early ZGA to varying degrees.…”
Section: Discussionmentioning
confidence: 94%
“…For the knockdown groups, the sequences of the small interfering RNAs (siRNAs) was the same with previous study ( Jiang et al, 2023b ). YBX1 siRNA (50 μM) was microinjected into the cytoplasm of a parthenogenetically activated oocyte via an Eppendorf Femto-Jet (Eppendorf, Hamburg, Germany) and Nikon Diaphot Eclipse TE300 inverted microscope (Nikon, Tokyo, Japan) equipped with the Narishige MM0-202N hydraulic 3-dimensional micromanipulator (Narishige, Amityville, NY, United States).…”
Section: Methodsmentioning
confidence: 99%